The effect of a structured exercise program implemented within 24 hours after extubation on selected outcomes following coronary artery bypass graft surgery - Klopper, Margareet (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhys) -- University of Stellenbosch, 2006.